Thyroid function test in abnormal uterine bleeding - Kattel, Pramod (Nepal Journal of Obstetrics and Gynaecology, 2018)
Aims: To evaluate and detect the thyroid dysfunction in patients with abnormal uterine bleeding (AUB) from puberty to menopause. Methods: This is an observational descriptive study of 90 patients of abnormal uterine bleeding at Paropakar Maternity and Women’s Hospital, Kathmandu from 17th January 2016 to 16th January 2017. Besides thyroid function test Pap smear, endometrial biopsy and histo-pathological examination of uterus following hysterectomy was done in selected cases. Results: The incidence of AUB was 6.2 % with mean age of 37 years. The most common presenting complaint was menorrhagia (36.7%) followed by metrorrhagia (23.3%). Thyroid dysfunction accounted for 20% of AUB with major share occupied by subclinical hypothyroidism (11%) and least by hyperthyroidism (1%). The most common association of thyroid dysfunction with AUB was overt hypothyroidism (27.3%) with menorrhagia. Non-structural cases of AUB accounted for 30.4% of thyroid dysfunction. Conclusions: This study shows that thyroid dysfunction plays significant role for AUB so it is wise enough to perform TFT on routine basis in order to avoid unnecessary hormonal treatment with Estrogen, Progesterone or their combination and even the hysterectomies.